2000
DOI: 10.1037/0893-164x.14.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Consequences Questionnaire—Spanish.

Abstract: A total of 212 Spanish smokers completed a Spanish version of a smoking questionnaire based on the Smoking Consequences Questionnaire--Adult (A. L. Copeland, T. H. Brandon, & E. P. Quinn, 1995) and a nicotine dependence (ND) measure. Confirmatory factor analysis results supported an a priori defined 8-factor structure. The results also indicated good internal consistency for the instrument and the scales derived from each factor. Positive outcome smoking expectancies scales were significantly and substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 42 publications
2
45
3
Order By: Relevance
“…Contrary to previous research on adult smokers (Brandon & Baker, 1991;Cepeda-Benito & Ferrer, 2000;Copeland et al, 1995), our analyses showed no significant gender differences on the scale scores. Future research should continue to assess for gender differences on the ASCQ scale scores, particularly among older adolescents and adolescents who smoke regularly.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Contrary to previous research on adult smokers (Brandon & Baker, 1991;Cepeda-Benito & Ferrer, 2000;Copeland et al, 1995), our analyses showed no significant gender differences on the scale scores. Future research should continue to assess for gender differences on the ASCQ scale scores, particularly among older adolescents and adolescents who smoke regularly.…”
Section: Discussioncontrasting
confidence: 86%
“…In several studies on the SCQ, analyses revealed evidence of good internal consistency, high factor loadings, and coefficient alphas ranging from .72 to .97. Construct and predictive validity have been supported by associations with smoking status (Brandon & Baker, 1991;Copeland et al, 1995), symptoms of dependence (Brandon & Baker, 1991;Cepeda-Benito & Ferrer, 2000;Copeland et al, 1995), withdrawal severity (Wetter et al, 1994), presence of negative affect (Copeland et al, 1995), and smoking rate after cessation treatment (Copeland et al, 1995;Wetter et al, 1994).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This construct has been assessed as it relates to cigarette smoking using the Smoking Consequences Questionnaire (SCQ; Brandon & Baker, 1991;Downey & Kilbey, 1995;Wetter et al, 1994) and the Smoking Consequences QuestionnaireAdult (SCQ-A; Copeland, Brandon, & Quinn, 1995). These measures assess both immediate and distal positive and negative smoking outcome expectancies, which vary with smoking status and gender and have shown evidence of predictive validity (Brandon & Baker, 1991;Buckley et al, 2005;Cepeda-Benito & Reig-Ferrer, 2000;Copeland et al, 1995;Jeffries et al, 2004;Myers, MacPherson, McCarthy, & Brown, 2003;Wetter et al, 1994). Both measures indicate that smokers tend to endorse positive outcomes to a greater extent than do nonsmokers or ex-smokers.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, we located only two investigations of the psychometric characteristics of the SCQ-A within at-risk or diverse populations (Cepeda-Bonito & Reig Ferrer, 2000;Jeffries et al, 2004). Given the marked elevation in smoking prevalence among individuals diagnosed with psychiatric problems relative to the general population (Hughes 1993;Hughes, Hatsumaki, Mitchell, & Dahlgreen, 1986;Lasser et al, 2000), studies examining smoking onset, maintenance, and cessation among psychiatric populations are of paramount importance.…”
Section: Introductionmentioning
confidence: 99%